A window into the early evolutionary history of Cercopithecidae: Late Miocene evidence from Chad, Central Africa - (:unkn) unknown (My University, 2019)
Central Africa is known as a major center of diversification for extant Old World Monkeys (OWM) and yet has a poorly documented fossil record of monkeys. Here we report a new colobine monkey (Cercopithecoides bruneti sp. nov.) from the Central African hominin-bearing fossiliferous area of Toros-Menalla, Chad at ca. 7 Ma. In addition to filling a gap in the spatial and temporal record of early OWM evolutionary history, we assess the ecomorphological diversity of early OWM by providing evidence on the onset of a folivorous diet and a partial reacquisition of terrestrial locomotor habits among Miocene colobines. We also support the phylogenetic affinities of the genus Cercopithecoides among the stem group of the extant African colobine monkeys.
Keywords: African Research